Assistance with cost management and digital promotion for the 'Fatih' photocopy business - Pristin Prima Sari; Nurul Myristica Indraswari; Agustinus Eko Susetyo; Salma Salsabila Iswandari; Laras Ayu Wulandari (Universitas Muhammadiyah Magelang, 2023)
Cost management is essential for the Fatih Photocopy business because daily data collection on raw materials and supplies is conducted. The primary goal of this community service is to impart knowledge about cost management and how to implement cost management formats and digital promotions for the Fatih Photocopy business. The program involves training and hands-on practice. The outcome of this program is an improved understanding of cost management formats among partners, enabling them to generate cost reports and enhance their digital promotion skills by maximizing the potential of social media.